Is exercise a match for cold exposure? Common molecular framework for adipose tissue browning - Martin, A. R.; Chung, S.; Koehler, K. (International Journal of Sports Medicine, 2020)
Exercise is commonly utilized for weight loss, yet research has focused less on specific modifications to adipose tissue metabolism. White adipose tissue (WAT) is the storage form of fat, whereas brown adipose tissue (BAT) is a thermogenic tissue whose uncoupling increases energy expenditure. The most established BAT activator is cold exposure, which also transforms WAT into "beige cells" that express uncoupling protein 1 (UCP1). Preliminary evidence in rodents suggests exercise elicits similar effects. The purpose of this review is to parallel and examine differences between exercise and cold exposure on BAT activation and beige induction. Like cold exposure, exercise stimulates the sympathetic nervous system and activates molecular pathways responsible for BAT/beige activation, including upregulation of BAT activation markers (UCP1, proliferator-activated receptor-gamma coactivator-1a) and stimulation of endocrine activators (fibroblast growth factor-21, irisin, and natriuretic peptides). Further, certain BAT activators are altered exclusively by exercise (interleukin-6, lactate). Markers of BAT activation increase from both cold exposure and exercise, whereas effects in WAT are compartment-specific. Stimulation of endocrine activators depends on numerous factors, including stimulus intensity and duration. Evidence of these analogous, albeit not mirrored, mechanisms is demonstrated by increases in adipose activity in rodents, while effects remain challenging to quantify in humans.